Written Corrective Feedback Provided by the Teacher on Student's Descriptive Writing for Fostering Student's Writing Quality - Sa'adah, Lailatus (RETAIN, 2022)
Written corrective feedback is an effective element in a student’s writing process. Therefore, the role of the teacher in giving written feedback on student’s composition is essential since it can assist them to be aware of the error that they have been made, learn about the error, and revise it into the correct form. In conducting this research a qualitative method was employed. The object of this research is the first draft and the final draft of the English Department student's descriptive writing. The researcher used only one student’s descriptive writing that has been rectified by the teacher using written corrective feedback to be analyzed in detail. This research aimed to explain some types of teacher’s written corrective feedback on student’s descriptive writing for fostering student’s writing quality. In this research, documentation was used as an instrument. This research showed that there were two types of feedback given to the student’s work; twelve errors were corrected by using direct written corrective feedback and four errors were corrected by using metalinguistic feedback. The teacher underlined, circled, crossed, and even gave written comments near the errors made by the student. Moreover, after looking at the student’s revised composition, it can be concluded that the students received all the feedback given by the teacher well. It increased student’s self-correcting which had a big impact on improving the quality of student's writing. Keywords: written corrective feedback, student’s composition, descriptive text.